2002
DOI: 10.1109/titb.2002.802372
|View full text |Cite
|
Sign up to set email alerts
|

Virtual-reality-based multidimensional therapy for the treatment of body image disturbances in binge eating disorders: a preliminary controlled study

Abstract: The main goal of this paper is to preliminarily evaluate the efficacy of a virtual-reality (VR)-based multidimensional approach in the treatment of body image attitudes and related constructs. The female binge eating disorder (BED) patients (n = 20), involved in a residential weight control treatment including low-calorie diet (1200 cal/day) and physical training, were randomly assigned either to the multidimensional VR treatment or to psychonutritional groups based on the cognitive-behavior approach. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 43 publications
1
52
0
1
Order By: Relevance
“…We also observed this adherence to treatment effect in other research using new technologies such as VR . The data in this study supports the effectiveness of VR compared to ''traditional'' strategies, especially in the treatment of body image disturbances (Perpiñ á et al, 2001;Riva et al, 2002). The features of this tool seem compatible with the therapeutic requirements of these highly complex disorders.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We also observed this adherence to treatment effect in other research using new technologies such as VR . The data in this study supports the effectiveness of VR compared to ''traditional'' strategies, especially in the treatment of body image disturbances (Perpiñ á et al, 2001;Riva et al, 2002). The features of this tool seem compatible with the therapeutic requirements of these highly complex disorders.…”
Section: Discussionsupporting
confidence: 78%
“…Information and Communication Technologies (ICT) are widely used as therapeutic tools in the field of neuropsychology (Rizzo et al, 1998) and also in the treatment of anxiety disorders: acrophobia (North and North, 1996), agoraphobia (North et al, 1997), spider phobia (Carlin et al, 1997), fear of public speaking (North et al, 1998), claustrophobia and eating disorders (Perpiñ á et al, 1999;Riva et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Riva and his colleagues [31,39] found that, in ED patients, a treatement including VR and ECT reduces binge eating, anxiety, and preoccupations having to do with being judged by others. It also improves body satisfaction, self-acceptance, self-esteem, self-efficacy, social functioning, as well as motivation to change.…”
Section: Efficacy Of Virtual Reality Focusing On Body Image In Ed Womenmentioning
confidence: 99%
“…It is not the scope of this chapter to offer a comprehensive review of these applications, but we mention some of them as follows (but see Glantz et al, 2003 andKrijn et al, 2004 for reviews). Experiential Cognitive Therapy was developed by Giuseppe Riva and his colleagues (Riva, 1998;Riva et al, 1999;Riva et al, 2002) to address obesity and eating disorders, particularly body image disturbance and the negative emotions associated with it. The VR component is integrated into a CBT approach and it consists of exposing patients to critical contexts and stimuli (e.g., kitchen, restaurant, commercials) and helping them deal with their emotional reactions and develop adaptive coping strategies.…”
Section: Vr Contributions To Intervention and To The Understanding Ofmentioning
confidence: 99%
“…Patients' false assumptions about their own body are also confronted in the virtual environment. The authors report positive results of this strategy, particularly in which body dissatisfaction and self-efficacy are concerned (Riva et al, 2002). More recently, it has been suggested that VR application could be developed not only for the assessment (see above), but also for the treatment of patients diagnosed with psychotic disorders.…”
Section: Vr Contributions To Intervention and To The Understanding Ofmentioning
confidence: 99%